PENGARUH PENYULUHAN TERHADAP TINGKAT PENGETAHUAN MASYARAKAT MENGENAI MALARIA DI DESA TERTONG KECAMATAN SINTANG TAHUN 2013 - ., Riana Suwarni (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: The incidence of malaria in the district of Sintang alwayshigh every year. The high incidence of malaria can be caused by poorpreventive measure of malaria due to lack of knowledge about malaria sothat the effort to increase knowledge is necessary through healtheducation. This research aims to determine the effect of health educationon the level of knowledge. Method: The study design was a quasiexperimentaldesign with a non-randomized control group pretest-posttest.A cluster sampling technique was used in choosing the required samplesfor this study. The samples in the control group was 62 peoples and theexperimental group of was 62 peoples. Intervention was only given to theexperimental group. A questionnaire was used to collect relevantinformation. The data were processed using the chi square test and themarginal homogeneity test. Result: There was significant posttestdifference between control group with the experimental group (p=0.000).There was a significant difference between pretest with posttest in theexperimental group (p=0.000). Conclusion: The final level of knowledgein community that got health education were higher than the level ofknowledge in community that did not get health education. There was anincreasing knowledge in community that got health education.